2010
DOI: 10.1016/j.hal.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Florida red tide perception: Residents versus tourists

Abstract: The west coast of Florida has annual blooms of the toxin-producing dinoflagellate, Karenia brevis with Sarasota, FL considered the epicenter for these blooms. Numerous outreach materials, including Frequently Asked Question (FAQ) cards, exhibits for local museums and aquaria, public beach signs, and numerous websites have been developed to disseminate information to the public about this natural hazard. In addition, during intense onshore blooms, a great deal of media attention, primarily via newspaper (print … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
(33 reference statements)
0
24
0
Order By: Relevance
“…Among other findings, the results indicated that coastal residents and tourists may not have efficiently delivered and up-to-date information about Florida red tides and their impacts because of inconsistent public outreach. Nierenberg et al, (in press) further pursued these issues assessing the public knowledge about Florida red tide. Again gaps in public knowledge regarding Florida red tides were identified, even among coastal residents; and preferred information sources for obtaining information on Florida red tide were also identified.…”
Section: 0 Monitoring Surveillance Outreach and Educationmentioning
confidence: 99%
“…Among other findings, the results indicated that coastal residents and tourists may not have efficiently delivered and up-to-date information about Florida red tides and their impacts because of inconsistent public outreach. Nierenberg et al, (in press) further pursued these issues assessing the public knowledge about Florida red tide. Again gaps in public knowledge regarding Florida red tides were identified, even among coastal residents; and preferred information sources for obtaining information on Florida red tide were also identified.…”
Section: 0 Monitoring Surveillance Outreach and Educationmentioning
confidence: 99%
“…Research has indicated “knowledge gaps” and misperceptions exist (Kirkpatrick et al, 2014; Nierenberg et al, 2010). While there has been much controversy in both the scientific community as well as the general public about formation of Florida red tides, past research indicates that finding accurate information has been a challenge for residents and visitors and that efforts are needed to educate the public about Florida red tide (Kirkpatrick et al, 2014; Nierenberg et al, 2010). …”
mentioning
confidence: 99%
“…Closings are also issued under emergency conditions such as for hurricanes or tropical storms (FDACS, 2014). Nierenberg et al (2010) noted that both Florida residents and tourists have only limited knowledge about red tide blooms and their effects, including the misconception that harvesting and eating shellfish during a red tide may be safe. Tourists were found to have even less knowledge about red tides than residents.…”
Section: Discussionmentioning
confidence: 99%